2018
DOI: 10.1007/s11663-018-1306-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Model of Basic Oxygen Steelmaking Process Based on Multizone Reaction Kinetics: Modeling of Manganese Removal

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The studies have shown at which levels of carbon and the time period a slag may maintain its lower density state before it is likely to begin decent back into the bulk bath. [64,[77][78][79][80] Due to the size of the specimens being studied and the capabilities of the setups, there has been a limitation in the visual output due to the metallic phase scattering X-ray and significant mobility within the samples. To improve the understanding, the present authors have taken an approach to fine-tune these trials to produce clearer images to inform high-accuracy quantitative evaluations of the decarburization for improving understanding and application to fundamentally driven dynamic process models.…”
Section: Gas Phase Production Effects On Free Steel Dropletsmentioning
confidence: 99%
“…The studies have shown at which levels of carbon and the time period a slag may maintain its lower density state before it is likely to begin decent back into the bulk bath. [64,[77][78][79][80] Due to the size of the specimens being studied and the capabilities of the setups, there has been a limitation in the visual output due to the metallic phase scattering X-ray and significant mobility within the samples. To improve the understanding, the present authors have taken an approach to fine-tune these trials to produce clearer images to inform high-accuracy quantitative evaluations of the decarburization for improving understanding and application to fundamentally driven dynamic process models.…”
Section: Gas Phase Production Effects On Free Steel Dropletsmentioning
confidence: 99%
“…In addition, the oxygen partial pressure in BOF slags may not be homogeneous, especially in view of it being a top blowing process: Slag regions surrounding the hot spot (where oxygen gas is in direct contact with the metal bath) may have a higher p(O 2 ) than those in contact with a CO‐containing gas phase (product of the decarburization reaction). Some works considered that the p(O 2 ) in slag regions surrounding the hot spot may reach values as high as 1 atm …”
Section: Discussion Of Ternary Oxide Systems Relevant To Bof Slagsmentioning
confidence: 99%
“…The details of the development of the global model and its validation with the industrial data are presented in this paper, while the kinetic models of decarburization and demanganisation are described in separate papers. [20,21]…”
Section: Figure 1: Schematic Representation Of Reactions In Bof Convertermentioning
confidence: 99%
“…[25,26] The detail mathematical model for C, Si and Mn oxidation kinetics in jet impact zone can be found elsewhere. [20,21,27] The interfacial area was assumed to be the area of the cavity created by the top jet. The surface area of the jet impact was considered to be paraboloid in shape [28] and was calculated as a function of lance height and oxygen flow rate.…”
Section: Jet Impact Zonementioning
confidence: 99%